IT utilization rate when determining corporate strategic goals - Hajkrová, Romana (Univerzita Pardubice, 2017)
This article assesses current level of the information support tools for a specific area of the corporate process. Under this area we understand strategic planning and determination of corporate strategic goals. The mentioned area is perceived quite differently by the plant owner than for instance employee of the same company. But the fact is that this area is the major axis that passes through the entire corporate structure and, if set correctly, it is the very key to success and especially to long-term development and stability of the company. From the historical point of view, creation of corporate strategic objectives was a certain foretelling from the crystal ball for a number of managers, depending on the corporate life cycle phase, or stereotypical raising the goals. Based on this way created corporate strategic goals, it is not surprising that fulfilment of these objectives reflects the reality rather by accident in many cases. Creating truly realistic strategic goals of the company with respect to its life cycle is a much more complex process and therefore one wonders at the low level of responsibility applied by certain managers to it.
Keywords: information technologies; strategic goals; strategic plans; company / plant; software; analysis; M15; M21